EFEKTIVITAS MEDIA PEMBELAJARAN GAMBAR BERSERI DALAM MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA SEKOLAH DASAR - Ilyas, Wandy Setiawan; Pramono, Imam Catur (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The low narrative writing skills of elementary school students, stemming from a lack of effective and engaging teaching methods. The main objective of this study is to evaluate the effectiveness of using serial picture media in improving elementary students' narrative writing skills. This research employs a literature review approach, analyzing various relevant scientific sources to draw insights from previous findings. Data collection methods involve documentation techniques, utilizing journals, books, and scientific articles as instruments. The data analysis method used is content analysis. The findings indicate that the use of serial pictures significantly enhances writing skills, including narrative structure, language use, and student creativity. Additionally, student motivation for learning increases with this media. The conclusion of this study underscores the importance of implementing serial pictures in writing instruction and suggests developing digital resources to address access and resource challenges. This research implies the need for collaboration among teachers, schools, and communities to provide adequate support.